Pilot study on the e-Kayak System: A wireless DAQ suited for performance analysis in flatwater sprint kayaks - Bonaiuto, V.; Gatta, G.; Romagnoli, C.; Boatto, P.; Lanotte, N.; Annino, G. (Sensors, 2020)
Nowadays, in modern elite sport, the identification of the best training strategies which are useful in obtaining improvements during competitions requires an accurate measure of the physiologic and biomechanical parameters that a ect performance. The goal of this pilot study was to investigate the capabilities of the e-Kayak system, a multichannel digital acquisition system specifically tailored for flatwater sprint kayaking application. e-Kayak allows the synchronous measure of all the parameters involved in kayak propulsion, both dynamic (including forces acting on the paddle and footrest) and kinematic (including stroke frequency, displacement, velocity, acceleration, roll, yaw, and pitch of the boat). After a detailed description of the system, we investigate its capability in supporting coaches to evaluate the performance of elite athletes` trough-specific measurements. This approach allows for a better understanding of the paddler`s motion and the relevant e ects on kayak behavior. The system allows the coach to carry out a wide study of kayak propulsion highlighting, and, at the same time, the occurrences of specific technical flaws in the paddling technique. In order to evaluate the correctness of the measurement results acquired in this pilot study, these results were compared with others which are available in the literature and which were obtained from subjects with similar characteristics.